The Path to Serenity: Benefits of Yoga and Meditation Based on Buddha Approach - Shrestha, Eka Bahadur (GS WOW: Wisdom of Worthy Research Journal, 2024)
The ancient practices of yoga and meditation, dating back 2,600 years to the teachings of the Buddha, have endured the test of time and gained widespread popularity in modern society for their numerous physical and mental health benefits. This paper explores the origins of yoga and meditation within Buddhist philosophy and examines the scientific evidence supporting their efficacy as mind-body therapies. Rooted in the pursuit of enlightenment and the cessation of suffering, the Buddhist traditions of yoga and meditation promote self-awareness, emotional regulation, and a profound sense of inner peace. Recent research has shed light on the neurological and physiological mechanisms underlying these practices, revealing their potential to reduce stress, alleviate anxiety and depression, improve sleep quality, and enhance overall well-being. Through a comprehensive exploration of the Buddha's teachings and the latest empirical evidence, this paper underscores the profound impact of yoga and meditation on cultivating serenity, fostering resilience, and unlocking the innate human capacity for greater mindfulness and compassion as it improves flexibility and cardiovascular health to reduced stress and anxiety, these practices offer a wide range of benefits that can improve overall health and well-being. Yoga’s incorporation of mediation and breathing can help improve a person’s mental well-being. Regular yoga practice creates mental clarity and calmness, increases body awareness, relieves chronic stress patterns, relaxes the mind, centres attention, and spares connection.